Who captures value from hackathons? Innovation contests with collective intelligence tools bridging creativity and coupled open innovation - Issam Attalah; Petra A. Nylund; Alexander Brem (Creativity and Innovation Management, 2023)
Balancing value creation and value capture is a fundamental strategic issue for the management of open innovation. Insufficient compensation for created value may hinder the participation of a firm or individual in open innovation. It can thus provide an obstacle to the open innovation process as a whole. Hackathons provide an attractive setting for studying value appropriation in open innovation by actors of different types and with varying bargaining power. We define hackathons as idea competitions on specific topics in the form of a time-limited event. These competitions have gained more popularity throughout the years and have recently become more prominent. Therefore, an abductive empirical study was carried out in an international set-up with multiple embedded cases of hackathons. Results indicate that hackathons offer coupled open innovation processes. The value captured by the initiator of a hackathon in the form of inbound open innovation is balanced by outbound knowledge flows towards participants as well as with sideways knowledge flows between participants, which are a result of the generation of collective intelligence. Collective intelligence is thus identified as an alternative mechanism for value capture from open innovation.
Keywords: 330; collective intelligence; creativity; hackathon; innovation; open innovation; value capture